Influence of Grating Time on Success of Soft Wood Grafting in Mango under Coastal Andhra Pradesh - Rani, K. Radha (International Journal of Economic Plants, 2025)
The experiment was conducted during August, 2023 to March, 2024 at Mango Research Station, Dr. YSR Horticultural University, Nuzvid, Andhra Pradesh, India to study the effect of grafting time on success of soft wood grafting in mango. The experiment consisted of 2 factors i.e grafting time and varieties with 3 replications and laid out in a two factorial Randomized Block Design (FRBD). The results indicated that among the treatments, bud break (14.2 days) was observed early on 10th September (17.5 days) while grafting done in 10th October took more days for bud break (18.8 days). However, graft success and survivability percentage was found highest (86.3 and 70.8% respectively) in October grating. Among the varieties, percentage of graft success and survivability were significantly highest (>80% and >60% respectively) in all varieties except Royal Special which recorded 77.9% of graft success and 59.9% of survivability. The interaction effects showed that graft success per cent was found significantly highest in Totapuri grafted on 10th October (91.7%) which was on par with Chinnarasam grafted on 10th August (88.7%), 10th October (86%) and Baneshan grafted on 10th October (88.3%). Graft survivability percentage was significantly highest in Chinnarasam (74.7%). Baneshan (73%) and Totapuri (70.7%) grafted on 10th October. The findings of this experiment clearly indicated that soft wood grafting done in the month of October was effective for graft success and survivability under coastal Andhra Pradesh.